Response of human intestinal lamina propria T lymphocytes to interleukin 12: additive effects of interleukin 15 and 7. Issue 5 (1st November 1998) - Monteleone, G; Parrello, T; Luzza, F; Pallone, F
Abstract : Background/Aim —Interleukin (IL) 12 is involved in the mucosal response during intestinal inflammation but its role is not fully understood. The response of human lamina propria T lymphocytes (T-LPL) to IL-12 in terms of interferon γ (IFN-γ) release and proliferation was investigated, exploring whether IL-15 and IL-7 cooperate with IL-12. The role of accessory molecules (CD2 and CD28) was also investigated. Methods —Unstimulated and phytohaemagglutinin preactivated T-LPL cultures were incubated with or without the initial addition of cytokines, anti-CD2 or anti-CD28 antibodies. IFN-γ mRNA was detected by reverse transcriptase polymerase chain reaction, and protein secretion was measured by enzyme linked immunosorbent assay (ELISA). Results —IFN-γ mRNA was induced in T-LPLs by IL-12 and IL-15 but not IL-7, whereas IFN-γ was measured only in IL-12 stimulated T-LPL cultures. IL-12 induced IFN-γ release was not abrogated by neutralising anti-IL-2 antibody or by cyclosporin A. IL-12 synergised with either anti-CD2 or anti-CD28 antibodies in inducing IFN-γ synthesis. In preactivated T-LPLs, IL-7 enhanced IFN-γ release induced by both IL-12 and anti-CD2, whereas IL-15 potentiated only IL-12 induced IFN-γ synthesis. IL-12 did not induce proliferation of either unstimulated or preactivated T-LPLs and it did not enhance the CD2/CD28 stimulated T-LPL proliferative response. No transcript for IL-12 receptor β1 subunit was detected in freshly isolated and activated T-LPLs whereas the β2 subunit mRNA was consistently found in T-LPL samples. Conclusions —IL-12 induces human T-LPLs to produce and release IFN-γ, and IL-15 and IL-7 cooperate with IL-12 in expanding the IFN-γ mucosal response.